Coherent X-ray diffraction imaging and characterization of strain in silicon-on-insulator nanostructures - Xiong, Gang (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.